Reduction of Pyrazine Oxide, free and coordinated to Ruthenium(II) - Blesa, Miguel Ángel; Taube, H. (American Chemical Society, 1975)
Fil: Blesa, Miguel Ángel Comisión Nacional de Energía Atómica; Argentina